Dynamic Stability Analysis of an Adjustable-Height Single-Arm Mobile Manipulator - Yuan, Tianqun; Shi, Xiumin; Qi, Yuming (International Journal of Mechanical and Electrical Engineering, 2025)
This study investigates the overturning stability of a self-developed, adjustable-height single-arm mobile manipulator during operations involving height variations and load-bearing tasks. Static and dynamic stability analyses were conducted to evaluate system performance. Under no-load and low-speed conditions, static stability was assessed using the gravity method. For typical operational scenarios with variable loads and changing arm heights, a dynamic stability criterion based on the Tip-Over Moment (TOM) was proposed, accompanied by the establishment of a system dynamics model and a comprehensive evaluation framework incorporating mean value and standard deviation metrics. Through co-simulations in MATLAB and ADAMS, the dynamic performance was examined under various combinations of load mass and manipulator height. Results indicate that the system maintains stability across all tested conditions. Increasing the load mass was found to enhance system stability, while elevating the arm height, despite improving the overall anti-overturning tendency, was observed to amplify moment fluctuations. This research provides a theoretical foundation for structural optimization and stable motion control of this class of adjustable-height single-arm mobile manipulators.